Collaborative Demonstration Method: An Effective Strategy to Enhance Science Learning Outcomes in Grade 4 - Fratiwi, Nuzulira Janeusse; Ersandi, Dedi (Jurnal Ilmu Manajemen dan Pendidikan, 2024)
This study was motivated through the low science learning outcomes of fourth-grade students, caused by a lack of variety in teaching methods, which made the learning process monotonous and resulted in minimal interaction between teachers and students. The study aimed to improve fourth-grade students’ science learning outcomes through the application of the Collaborative Demonstration Method. The research was conducted on 24 fourth-grade students, consisting of 12 male and 12 female students, over two cycles that included planning, implementation, observation, and reflection phases. Data were collected through observation sheets, learning outcome tests, and student response questionnaires. The analysis showed that in Cycle I, the students’ average score was 69.5, with 16 students meeting the learning criteria and 8 students not yet meeting it, the highest score being 85 and the lowest 50. In Cycle II, all students achieved mastery, with an average score of 81.7, the highest score of 95, and the lowest 65. Thus, the application of the Collaborative Demonstration Method was proven effective in improving the science learning outcomes of fourth-grade students. Teachers are encouraged to implement the collaborative demonstration method in teaching, especially in science subjects, to enhance interaction, understanding, and student learning outcomes.